2021
DOI: 10.1111/hae.14483
|View full text |Cite
|
Sign up to set email alerts
|

Do we need all that emicizumab?

Abstract: ing protection against bleeds. In both the inhibitor and non-inhibitor patients the remarkable improvement is evidenced in the real-world settings after the extensive clinical phase 3 studies. [1][2][3][4] After stopping the coadministration with activated prothrombin complex concentrate (aPCC, Feiba R ), only a small number of adverse events have been encountered, associated with thrombosis and some breakthrough bleeds. The immediate management option for possible breakthrough bleeds or trauma either with rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…The dose was reduced to result in emicizumab concentrations of ~24 µg/mL, after which the pain resolved and no bleeds occurred during the following 6 months. Subsequently, emicizumab was given in lower doses in 11 PwHA from Finland and 6 PwHA from Thailand without loss of efficacy 19 39. Additionally, real-world evidence from our centre demonstrated similar bleed rates across the concentration subgroups of <40 µg/mL (n=13), 40–80 µg/mL (n=59) and >80 µg/mL (n=22) 15.…”
Section: Discussionmentioning
confidence: 69%
“…The dose was reduced to result in emicizumab concentrations of ~24 µg/mL, after which the pain resolved and no bleeds occurred during the following 6 months. Subsequently, emicizumab was given in lower doses in 11 PwHA from Finland and 6 PwHA from Thailand without loss of efficacy 19 39. Additionally, real-world evidence from our centre demonstrated similar bleed rates across the concentration subgroups of <40 µg/mL (n=13), 40–80 µg/mL (n=59) and >80 µg/mL (n=22) 15.…”
Section: Discussionmentioning
confidence: 69%
“…7 Moreover, an individualized monitoring of emicizumab concentrations could be useful to optimize the injected dose and allow a more cost-effective dosing. 8 As already described in previously published data, 3 the action of emicizumab leads to a shortened aPTT due to the immediate action of emicizumab in the tenase complex. This effect on aPTT is dose-dependent and observed at low concentration of emicizumab (<13 µg/ml), from the first injection but offers false reassurance because it only reflects a moderate increase in haemostatic capacity.…”
mentioning
confidence: 66%
“…and an average maintenance dose of 1.3 mg/kg/every 2 weeks (43% of recommended) did very well with all, except for one patient, not experiencing any bleeds. 45 The other five published case series were all published in 2023.…”
Section: Low-dose Emicizumabmentioning
confidence: 99%
“…A case series from Finland published in 2022 demonstrated that 11 adult patients (three Inhibitor positive; eight inhibitor negative) receiving an average loading dose of 2.7 mg/kg/wk (90% of recommended) and an average maintenance dose of 1.3 mg/kg/every 2 weeks (43% of recommended) did very well with all, except for one patient, not experiencing any bleeds 45 …”
Section: Introductionmentioning
confidence: 99%